Modeling the economics of insecticide and trypanocide-treated cattle interventions against trypanosomiasis disease within a multi-host situation - Jamah, Tokpa Darwolo (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.